PENGARUH PERILAKU INDIVIDU TERHADAP KINERJA ORGANISASI: STUDI KASUS DI BENGKEL RESMI YAMAHA ARISTA SUBANG - Jojo jojo; Agus Ibrahim; Imelda Imelda; riska putri T; Mutqi Sopiawadi; Kuncorosidi Kuncorosidi (Gapura (Garba Pembangunan Masyarakat), 2025)
This research aims to analyze the influence of individual behavior on organizational performance at the Official Yamaha Arista Workshop. The research background is the important role of individual behavior such as attitude and motivation in the automotive service work environment, where human resources are the key to the success of company productivity. The method used is quantitative with a survey approach involving several employees as respondents. Data was collected through questionnaires and analyzed using multiple linear regression with the help of statistical software. The research results show that individual behavior does not have a significant positive effect on organizational performance. These findings do not confirm that developing employee behavior is a strategic step in improving service quality and company productivity. However, this research also provides practical implications for management to continue to pay attention to aspects of human resource development. The limitations of this research lie in the sample which only took one official workshop and the measurements were based on respondents' perceptions, so further research is needed with wider coverage and other additional variables.